Bilateral Morganella Morganii keratitis in a patient with facial topical corticosteroid-induced rosacea-like dermatitis: a case report - Bei Zhang (BMC Ophthalmology, 2017)
Abstract Background Bilateral keratitis rarely occurs in individuals without predisposing factors. Here we describe the clinical course of a patient who developed a bilateral keratitis caused by Morganella. morganii which might be associated with long term using of topical corticosteroids-containing preparations on the face. Case presentation A 52-year-old female patient presented with marked bilateral corneal infiltration and hypopyon without any usual predisposing factors for bilateral infectious keratitis. There was diffuse erythema with itching on face before the onset of eye discomforts. Microbiological culture of materials from both corneas revealed significant growth of Morganella morganii. Topical corticosteroid-induced rosacea-like dermatitis was diagnosed by dermatologist because of the characteristic eruptions and long history of using the corticosteroids-containing cosmetic creams on her face. The corneal ulcers responded well to levofloxacin eye drops and ofloxacin ointment and healed with opacity and neovascularization. Conclusion This case illustrates that bilateral bacterial corneal infection can develop in patients with long term using of topical corticosteroids-containing preparations on the face. To our knowledge, this is the first case of bilateral keratitis caused by Morganella morganii.